Characterization of Beta-Lactamases in Bloodstream-Infection Escherichia coli: Dissemination of blaADC–162 and blaCMY–2 Among Bacteria via an IncF Plasmid - Xiao, Linlin; Wang, Xiaotong; Kong, Nana; Zhang, Long; Cao, Mei; Sun, Muzhen; Wei, Quhao; Liu, Weiwei (Frontiers in Microbiology, 2019)
Objectives To describe the molecular characteristics of beta-lactamases in bloodstream-infection Escherichia coli isolated from elderly patients, and to determine the genotypic patterns of blaCMY–2 and blaADC–162. Methods A total of 50 bloodstream-infection E. coli isolates were obtained from patients aged > 50 years at Shanghai Sixth People’s Hospital South Campus during 2015–2018. The isolates were subjected to beta-lactamase detection using phenotypic and molecular methods. Beta-lactamase genes were verified by sequencing and the phylogenetic relationships of the isolates were analyzed by multilocus sequence typing (MLST). The transferability of plasmids carrying blaCMY–2 and blaADC–162 genes was verified by conjugation experiments and plasmid replicon typing. Results Eight beta-lactamase subtypes were detected in 50 isolates of bloodstream-infection E. coli. blaTEM–1 (21/50) was the most common beta-lactamase gene, followed by blaCTX–M–14 (8/50), blaOXA–27 (5/50), blaCTX–M–27 (3/50), blaCTX–M–65 (1/50), blaADC–162 (1/50), and blaCMY–2 (1/50). Of these, blaADC–162 (ST95-A), and blaCMY–2 (ST95-B2) have not previously been reported in bloodstream-infection E. coli. In 21 isolates, beta-lactamase genes were located on conjugative plasmids belonging to incompatibility groups FrepB (n = 7), FIA (n = 1), FIC (n = 2), K (n = 8), N (n = 1), and I (n = 1), and blaCTX–M was associated with the common elements ISEcp1, IS903, and IS26, but with special sequences (region V, region Y, and region W) for ISEcp1 in 14 isolates. Conclusion To the best of our knowledge, this study provides the first molecular characterization of beta-lactamase genes in E. coli isolated from the bloodstream in elderly patients. Beta-lactamase genes were detected at a relatively high frequency in elderly patients with bloodstream E. coli infections. Plasmid replicon analysis showed that horizontal dissemination of beta-lactamase genes was mainly mediated by IncK and IncF plasmids, which could encode multidrug resistance genes. The study also provides the first report of ISAba1-blaADC–162-tnpA and ISEcp1-blaCTX–M–14-IS903-blaCMY–2-blc-sugE in E. coli, and demonstrates IncF plasmid-mediated blaADC–162 and blaCMY–2 gene dissemination among bacteria.